1995
DOI: 10.21236/ada418658
|View full text |Cite
|
Sign up to set email alerts
|

Sonar Headphone Selection for Optimum Performance: An Overview

Abstract: Summary PageThe ProblemTo improve the real-time auditory detection and aural analysis capability of passive broadband sonar systems. The FindingsThe most blatant source of acoustic signal degradation on auditory sonar systems is in the acoustic performance of headsets. Recent detection performance data have shown the need for upgrading sonar headsets to reproduce electrical energy accurately over a wider bandwidth. Headphone measurement data on commercially available headphones have shown that headphones of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Since the overall level of the sea noise signal in the headset must be kept at a reasonably comfortable and safe level, these constraints result in airborne noise masking the low-frequency component of the target signal to be detected within the sea noise. This explains why previous reports (Russotti, 1993;Benedetto et al, 1995;Russotti, 1995) found improved sonar operator performance with ANC headsets. Should the target of interest have most of its radiated energy in these lower frequencies, the decrement in performance caused by the interference of this low-frequency airborne noise becomes even more detrimental.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Since the overall level of the sea noise signal in the headset must be kept at a reasonably comfortable and safe level, these constraints result in airborne noise masking the low-frequency component of the target signal to be detected within the sea noise. This explains why previous reports (Russotti, 1993;Benedetto et al, 1995;Russotti, 1995) found improved sonar operator performance with ANC headsets. Should the target of interest have most of its radiated energy in these lower frequencies, the decrement in performance caused by the interference of this low-frequency airborne noise becomes even more detrimental.…”
Section: Introductionmentioning
confidence: 76%
“…As a consequence, passive noise-occluding headsets, which require a good seal for noise attenuation, are not a desirable design for accurate sound reproduction. Tests of military and commercial headsets have found that noise-occluding headsets are also characteristically band-limited (Russotti, 1995). Such headsets were originally designed for communica-tions and are cost effectively band-limited to the speech range for that application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earpieces of the Littmann were carefully fitted into the ear canals of a Kemar ® manikin. This device, equipped with Zwislocki ear simulators that model the acoustic impedance of the ear, has been used extensively in our headphone research (25,26). Pliant bags of lead shot placed within the manikin were used to block sound transmission to the calibrated microphone "eardrum" from pathways other than the ear canals.…”
Section: Recording Of Vital-sounds Stimulimentioning
confidence: 99%
“…As a consequence, passive noise-occluding-earphone headsets, which require a good seal to occlude the ear canal for noise attenuation, are not a desirable design for accurate sound reproduction. Tests of military and commercial headsets have found that noiseoccluding earphones are also characteristically band-limited (Russotti, 1995). Such headsets were originally designed for communications and are cost effectively band-limited to the speech range for that application.…”
Section: Introductionmentioning
confidence: 99%